Changes tropical monsoon higt-stem forests in the Vietnam - KUZNETSOV, A. N.; KUZNETSOVA, S. P.; Hoi, Nguyen Dang (Academia Journal of Biology, 2012)
Tropical ecosystems are the major component of the biosphere rendering global influence to atmospheric conditions on our Planet and determining it well-being. Tropical forest communities are the most difficultly organized and rich of animal and plant species biological systems with internal cyclic of metabolism and regenerative processes. On a background of growing human intensification of tropical forest resources using profound and deep researches, understanding, monitoring and prognostic of reactions of tropical primary forest ecosystems on external and internal impact and destruction are represented extremely urgent now. Vietnam monsoon tropical forests are very ancient and evolutionary vegetative formations. A species composition of the tropical forests includes not less than 7000 plant species, from which more than 3000 species - trees. The greatest variety of plant species and complex vertical structure are characterizing for high-stem tropical forests. Tropical forest ecosystems represents the climatic climax and ones are in dynamic balance. This balance is determined internal and external infringements, evolutionally characteristic for these plant communities. For monsoon primary forests, natural kinds of tree canopy destructions are different forest gaps, which form as a result of fall down whole trees, break tree trunks, crowns or branches. Such phenomena as a burning or fire is not characterize for these forests. Strong storms are quiet rare events too. Forests in mountain there is a gravitation movement of a soft soil substratum or a solyphluction (landslide) is adding to gaps. Inside forest gap there is a change of a microclimate in a direction increasing insulation, temperatures of air and soil. A reforestation on gaps goes due to realization of adaptive abilities of forest trees and lianas with the minimal participation of pioneer plants. A restoration of the primary forest structure and plant species composition may be named like a demutate succession. Uses by the man for agriculture a small forest area (up to 2-4 ha) can be considered as the external factor initiating demutate succession process. However, a Man also is carrying into a tropical nature life such global destructions as cutting down and clearing on forest areas for fields and plantations and apotheosis of human destruction - military destruction forests by herbicide spraying, napalm and fire bombs during The Second Indochina war. Our research in primary and human-transformed tropical forest ecosystems in Southern, Central and Northern Vietnam has shown that forest reactions to human intervention are very specific. Reactions are determined by a complex of factors, in particular the species composition of plants, spatial structure of the forest community, presence of the main forest species of trees, phenology and physiology of forest plants, features of forest microclimate, relief, structure of the soil and its hydrology. The district Linh Thuong in province Quang Tri (Central Vietnam) - is one of the most destroyed during the War. To the present time, after more than thirty years after War grasslands, which were appeared on the place primary forests, have not undergone changes in the party of change by their tree or bush communities. Our researches in this area are proved. That, the occurrence not forest open territories has resulted in change of a microclimate, hydrological regime, properties of soil and development of erosive processes. So, in July - a most hot month - the day time temperatures of air under the forests canopy (on a point 120 cm above a surface of the ground) reached 33oC, whereas on grasslands the maximal meaning was 43oC. The temperature of a ground surface under the forest canopy rose up to 28oC, whereas on grasslands maximum was 36oC. The humidity of air under the forests canopy changed from 85 up to 100%, on grasslands - from 55 up to 95%. So, in result of the military influence to primary forests have appeared atonal savanna-like grassy communities. The complex and multi-species forest communities were replaced for the simple and mono-species communities. The main forest tree species and pioneer trees, by virtue of their biological features and changes of microclimate, are not adapted to growth and development on these territories. The global human destructions are occurred a reason of interruption successions in the forest ecosystems. The existence of such grassy communities is uncertainly long, since there are no factors - except a human factor, - capable to change a trend of their development. Using of these grassy areas for agricultural cultivation or planting forest cultures will be demanded the special scientific knowledge for development of competent and ecologically responsible technological receptions on a background of an investment of significant financial means.